2017
DOI: 10.1007/s10551-017-3692-2
|View full text |Cite
|
Sign up to set email alerts
|

Bystander Responses to Bullying at Work: The Role of Mode, Type and Relationship to Target

Abstract: Framed within theories of fairness and stress, the current paper examines bystanders' intervention intention to workplace bullying across two studies based on international employee samples (N = 578). Using a vignettebased design, we examined the role of bullying mode (offline vs. online), bullying type (personal vs. work-related) and target closeness (friend vs. work colleague) on bystanders' behavioural intentions to respond, to sympathise with the victim (defender role), to reinforce the perpetrator (prosec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 78 publications
1
54
1
Order By: Relevance
“…Other studies have suggested that workplace friends tend to help targets in bullying incidents (Brody and Vangelisti ; Coyne et al. ; D'Cruz and Noronha ). In the present case, however, the targets’ friends were able to provide only limited and low‐profile support.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Other studies have suggested that workplace friends tend to help targets in bullying incidents (Brody and Vangelisti ; Coyne et al. ; D'Cruz and Noronha ). In the present case, however, the targets’ friends were able to provide only limited and low‐profile support.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, because managers hold authority over the performance appraisals and promotions of employees, bystanders often choose to tolerate bullying behavior out of fear that they will become the next targets, as participants in the present study did. Other studies have suggested that workplace friends tend to help targets in bullying incidents (Brody and Vangelisti 2016;Coyne et al 2016;D'Cruz and Noronha 2011). In the present case, however, the targets' friends were able to provide only limited and low-profile support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bystanders to bullying can validate the experience of a target and assist and support the target, making their role particularly important in addressing workplace bullying (Coyne et al, 2019). Exploring the response of bystanders to workplace bullying based on target sexual orientation may uncover effective strategies to reduce the detrimental effects of this type of mistreatment in a marginalized workforce segment (Mulder, et al, 2017;Paull, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%